Covalent Carbide Interconnects Enable Robust Interfaces and Thin SEI for Graphite Anode Stability under Extreme Fast Charging - Yverick Rangom; Oleksii Sherepenko; Ahad Shafiee; Alek Cholewinski; Kiran Gundegowda Kalligowdanadoddi; Bersu Bastug Azer; Parisa Jafarzadeh; Boxin Zhao; Elliot Biro; Holger Kleinke; Michael A. Pope (Advanced Science)
Abstract Carbonaceous and carbon‐coated electrodes are ubiquitous in electrochemical energy storage and conversion technologies due to their electrochemical stability, lightweight nature, and relatively low cost. However, traditional reliance on conductive additives and binders leads to impermanent electrical pathways. Here, a general approach is presented to fabricate robust electrodes with a progressive failure mechanism by introducing carbide‐based interconnects grown via carbothermal conversion of (5 wt%) titanium hydride nanoparticles. This method concurrently enhances both electrical and mechanical properties within the electrode architecture. The resulting chemical bonding between active materials establishes a novel mechanism to maintain stable electrical pathways during cycling. Employed as Li‐ion battery anodes, these electrodes exhibit improved cyclability, achieving 80% capacity retention after 800 fast‐charge cycles at moderate loading (1 mAh cm−2). High loading cells with areal capacity of 3 mAh cm−2 show significantly improved cycle life over the same number of cycles. This performance improvement is attributed to the absence of significant impedance growth and a thinner solid electrolyte interphase (SEI) layer formed at high current densities (4C) as demonstrated by X‐ray photoelectron spectroscopy and transmission electron microscopy studies. The enhanced conductivity facilitates SEI formation, lowering ionic impedance and mitigating lithium plating, ultimately leading to the reported extended cycle life.